The use of synthetic phosphoethanolamine in cancer patients: a documentary analysis (Research, Society and Development, 2021)
Introduction- The approach on synthetic phosphoethanolamine (Pho-s) concerns the death of cancer-causing cells. The role of nursing involves perceiving the patient meanings of changes in values, beliefs and attitudes. Method - documentary research of qualitative, exploratory approach - retrospective descriptive through interviews and televised sessions of the House of The Senate and Deputies, as well as documentary and oral journalistic articles, with the use of an online platform. Results - the discussion process began with the chemist Gilberto Chierice, when he developed the substance in the 1980s. From events with Pho-s, such as distribution without proven clinical studies, the discussion was brought to court until receiving attention from federal parliamentarians, thereby advancing to legal means where a commission was organized to discuss. The bill was approved by federal deputies, authorizing the use and production of Pho-s. However, in the same year the Supreme Court suspended the law voted in the Senate for accuracy of further clinical analysis. Discussion – to correlate the complex picture of cancer is used in the pyramid of basic needs, Theory Wanda Horta. With the physiological dysfunction that has occurred manifestation of cancer the physiological part is compromised and thus the base of the pyramid is compromised. Nursing plays an important role in this process, restoring the balance of the individual and the restoration of the physiological part. Final considerations - the role of the multidisciplinary team to meet the demands of cancer patients is of great value for patient recovery.